Backpropagation algorithm for complex neural networks - Kotsovsky, V.; Geche, F.; Batyuk, A.; Mitsa, A. (Видавництво Львівської політехніки, 2012)
Розглянуто комплексні штучні нейронні мережі, функції активації яких є комплексними аналогами раціональної сигмоїди. Наведено алгоритм навчання цих мереж, заснований на методі зворотного поширення похибки. Neural networks with complex weights and continuously differentiable activation function have been studied in the paper. Learning algorithm based on the backpropagation method for rational sigmoid function has been given in the paper.
Keywords: штучний нейрон; штучні нейронні мережі; комплексні нейронні мережі; алгоритм зворотного поширення помилки; artificial neuron; artificial neural networks; complex neural networks; learning algorithms; backpropagation